PARTICIPATORY ACTION RESEARCH AS A METHOD THAT ENHANCES EDUCATION IN THE BASIC AND SECONDARY SCHOOL OF THE ALFONSO LÓPEZ PUMAREJO EDUCATIONAL INSTITUTION. VALLEDUPAR. COLOMBIA. - Cervera, Karina Paola Torres; Castro, Elkin Fabián García; Romero, Teovaldo García; Plata, Paola Fernanda Morales; Sidedor, Eduar José Florian (Journal of Posthumanism, 2024)
The objective of this work was to analyze participatory action research as a method that enhances education in elementary and middle school students of the Alfonso López Pumarejo Educational Institution, under a positivist epistemic approach, of a descriptive projective theoretical cut with a cross-sectional field design, not experimental. For its analysis, a population of thirty-four (34) teachers is considered, two (administrative staff officials and 1147 students, with an intentional sampling of sixteen (16) teachers, two (2) administrative staff and two hundred and sixty (260) students in 9th, 10th and 11th grade of elementary and middle school, with similar characteristics. The survey was used as a technique and a questionnaire with a Likert scale with 48 items was used as an instrument, validated by three experts, yielding a reliability in pilot test of 0.972 for teachers and 0.923 for students, both with very high reliability. Descriptive statistics and the correlation coefficient of 0.949 teachers and 0.986 students were used as an analysis technique. The results showed that the variable action research and participation for teachers yielded an average of 3.32 and 2.91 for students; While environmental education was presented in teachers 3.32 and in the case of students an average of 2.91, both neutral results, these averages, close to the midpoint of the scale used (which usually ranges from 1 to 5), suggest a ’neutral’ perception or implementation of both areas in the institution, according to the respondents. that is, they are not perceived in a very positive or very negative way; they could indicate indifference, lack of in-depth knowledge, or limited or unimpactful application of PAR and environmental education strategies in the school’s daily practice at the time. Hence, the need to establish pedagogical guidelines as a transversal axis in the curricula that reinforce competencies in both, transform the environmental culture of the institution and impact the ecosystem in general spreads.